2015
DOI: 10.1021/acscentsci.5b00174
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aerosol Particle Mixing State on the Hygroscopicity of Sea Spray Aerosol

Abstract: Aerosol particles influence global climate by determining cloud droplet number concentrations, brightness, and lifetime. Primary aerosol particles, such as those produced from breaking waves in the ocean, display large particle–particle variability in chemical composition, morphology, and physical phase state, all of which affect the ability of individual particles to accommodate water and grow into cloud droplets. Despite such diversity in molecular composition, there is a paucity of methods available to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 56 publications
2
70
0
Order By: Relevance
“…In general agreement with the bloom experiments presented herein, a recent study by Schill et al [2015] showed a lack of change in the CCN-derived hygroscopicity of SSA for experiments wherein various representative proxy compounds for marine organic matter were sequentially added to a MART containing artificial seawater, resulting in an ultimate organic matter concentration of 350 μM C. The final concentration of this "artificial bloom" experiment was similar to the total organic carbon concentration found in the phytoplankton bloom experiments in the present study ( Figure S1). Overall, studies using state-of-the-art SSA production methods that range from additions of a few simple proxy compounds to those utilizing complex, phytoplankton-based organic systems have illustrated a common range of CCN-derived hygroscopicity for freshly emitted SSA particles between κ app = 0.7-1.4.…”
Section: Hygroscopicity Of Sea Spray From Laboratory Phytoplankton Blsupporting
confidence: 92%
See 1 more Smart Citation
“…In general agreement with the bloom experiments presented herein, a recent study by Schill et al [2015] showed a lack of change in the CCN-derived hygroscopicity of SSA for experiments wherein various representative proxy compounds for marine organic matter were sequentially added to a MART containing artificial seawater, resulting in an ultimate organic matter concentration of 350 μM C. The final concentration of this "artificial bloom" experiment was similar to the total organic carbon concentration found in the phytoplankton bloom experiments in the present study ( Figure S1). Overall, studies using state-of-the-art SSA production methods that range from additions of a few simple proxy compounds to those utilizing complex, phytoplankton-based organic systems have illustrated a common range of CCN-derived hygroscopicity for freshly emitted SSA particles between κ app = 0.7-1.4.…”
Section: Hygroscopicity Of Sea Spray From Laboratory Phytoplankton Blsupporting
confidence: 92%
“…Using a plunging waterfall method, SSA particles were produced with physicochemical properties similar to those produced by breaking waves [Collins et al, 2014 The relative role of chemistry in determining CCN concentrations mostly centers on the magnitude of the change in κ app compared with the magnitude of possible changes in the number size distribution of aerosol [Dusek et al, 2006]. Rather than focusing on just the average composition of particles in the atmosphere, Wex et al [2010a] illustrated conceptually that the mixing state of the chemical components of the aerosol population is a key component of the system, which has been shown in laboratory [Collins et al, 2013;Schill et al, 2015], field [Cubison et al, 2008;Padro et al, 2012], and modeling studies Roelofs, 2008]. The strongest effect of composition in decreasing CCN activity occurs when the abundance of particle types, each with significantly different intrinsic hygroscopicity, vary with size and the less hygroscopic particles have smaller dry diameters than the more hygroscopic particles [Collins et al, 2013;Wex et al, 2010a].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the ability of an SSA particle to take up water is directly correlated with the hygroscopicity (represented by kappa [k] values) of the organic and inorganic fractions, where the overall particle hygroscopicity is a linear combination of the k values for each compound present. 60,61 In this study, k values calculated from laboratory measurements of particle hygroscopic growth factors of SSA mimics with a hygroscopic tandem differential mobility analyzer (HTDMA) show that surface-active species observed in SSA particles from the wave flume, such as long-chain fatty acids and polysaccharides, exhibit decreased hygroscopicity in relation to free saccharides (Table 1). These calculated k values help explain the observed changes in the average and range of hygroscopicities of individual SSA particles collected during the wave-flume experiment.…”
Section: Interparticle Variability Of Ssa and Influence On Hygroscopimentioning
confidence: 72%
“…37 Artificial blooms doped with proxy compounds for marine organic matter have yielded similar results. 36 The discord between the cloud forming ability and SSA composition was suggested to be driven by the influence of particle surface tension in defining cloud droplet activation. However, the role of surface tension in defining cloud droplet activation is currently under scrutiny, 38 and thus future laboratory studies are needed.…”
Section: ■ Chemistry-driven Interactions Betweenmentioning
confidence: 99%
“…These include using standard scales derived from reference chemical systems against which to compare gas entry through organic surface active species, 28 organic species detected in complex SSA to inform molecular-scale simulations to produce thermodynamic models that can use surface tension values to predict the morphology of liquid−liquid phase separated organic-containing aerosol, 41 and model SSA compounds to better predict CCN activation of distinct SSA particle types. 36 …”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%